2019
DOI: 10.1111/tpj.14365
|View full text |Cite
|
Sign up to set email alerts
|

TDR INTERACTING PROTEIN 3, encoding a PHD‐finger transcription factor, regulates Ubisch bodies and pollen wall formation in rice

Abstract: Summary Male reproductive development involves a complex series of biological events and precise transcriptional regulation is essential for this biological process in flowering plants. Several transcriptional factors have been reported to regulate tapetum and pollen development, however the transcriptional mechanism underlying Ubisch bodies and pollen wall formation remains less understood. Here, we characterized and isolated a male sterility mutant of TDR INTERACTING PROTEIN 3 (TIP3) in rice. The tip3 mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 69 publications
0
29
0
1
Order By: Relevance
“…GUS assays were conducted as described previously (Yang et al, 2019). The protocol of the H 2 DCFDA experiment was modified according to the method of Leshem et al (2006).…”
Section: Histochemical Marker Staining Assaymentioning
confidence: 99%
“…GUS assays were conducted as described previously (Yang et al, 2019). The protocol of the H 2 DCFDA experiment was modified according to the method of Leshem et al (2006).…”
Section: Histochemical Marker Staining Assaymentioning
confidence: 99%
“…Previous studies have suggested that the post‐meiotic developmental program of rice anthers is regulated by multiple transcription factors, such as TDR (Li et al ., 2006), GAMYB (Aya et al ., 2009), Undeveloped Tapetum 1 (UDT1) (Jung et al ., 2005), ETERNAL TAPETUM 1 (EAT1) (Niu et al ., 2013), OsMADS3 (Hu et al ., 2011), PERSISTENT TAPETAL CELL 1 (PTC1) (Li et al ., 2011), OsTDF1 (Cai et al ., 2015), TDR INTERACTING PROTEIN 2 (TIP2) (Fu et al ., 2014) and TIP3 (Yang et al ., 2019). Some of these proteins physically interact to finely regulate the development of the microspore and tapetum (Ono et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…TDR can also physically interact with a PHD‐finger transcription factor, TIP3. The complex containing TDR and TIP3 mainly regulates the formation of pollen exine in rice (Yang et al ., 2019). Here, we revealed that DMD1 can interact with TDR.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the gene TDR INTERACTING PROTEIN3 ( TIP3 ) encodes for a PHD-Finger TF that is expressed during early anther development. tip3 mutants are characterized by defective anther cuticle and pollen wall formation, an abnormal ubisch body morphology, and a delayed degradation of the tapetum ( Yang et al, 2019b ).…”
Section: Genetic and Biochemical Regulatory Mechanisms Of Gms Genesmentioning
confidence: 99%
“…The TDR Interacting Protein 2 ( TIP2 ) and TDR Interacting Protein 3 ( TIP3 ) genes follow the pathway of indirect regulation of target genes. Moreover, TIP2 and TIP3 regulate the expression of the Tapetum Degeneration Retardation ( TDR ) gene ( Fu et al, 2014 ; Ko et al, 2014 ; Yang et al, 2019b ), which, in turn, regulates the expression of other target genes, including OsC6 and OsCYP703A3 , by directly binding to their promoter. Similarly, the gene TGA10 interacts with both TIP2 and TDR and affects the expression of AP25 and MTR1 genes ( Chen et al, 2018 ).…”
Section: Genetic and Biochemical Regulatory Mechanisms Of Gms Genesmentioning
confidence: 99%